Genome-wide transcriptional analyses of Chinese patients reveal cell migration is attenuated in IDH1-mutant glioblastomas. Issue 2 (28th February 2015) - Hu, Huimin; Wang, Zheng; Liu, Yanwei; Zhang, Chuanbao; Li, Mingyang; Zhang, Wenlong; Wang, Kuanyu; Cai, Jinquan; Cheng, Wen; Huang, Hua; Jiang, Tao
Highlights: We aimed to explore the mechanisms underlying different outcomes of IDH1 WT and IDH1 mutated glioblastomas (GBMs) through analysis of genes differential expression. New findings were as follows. Transcriptional differences between IDH1 mutant and wild type GBMs derived from 69 Chinese patients revealed compromised focal adhesion in IDH1 mutant GBMs. GBM cells stably expressing mutated IDH1 showed diminished adhesion between each other and less cell aggregation. The reported downstream of IDH1 and the important modulator of cell adhesion and migration, HIF1α, was found affected by IDH1 mutation. Abstract: Patients with isocitrate dehydrogenase 1 ( IDH1 )-mutant glioblastoma exhibit increased survival compared with those with wild-type IDH1 tumors. The magnitude of this finding has led to the use of IDH1 mutations as diagnostic and prognostic biomarkers. However, the mechanisms underlying the reported correlation between the IDH1 mutation and increased survival have not been fully revealed. In this work, based on genome-wide transcriptional analyses of 69 Chinese patients with glioblastoma, we have found that the focal adhesion pathway is significantly downregulated in IDH1 -mutant glioblastomas. The impaired focal adhesion leads to compromised cell migration and tumor invasion, contributing to the optimistic prognosis of these patients. Moreover, the signature genes of HIF-1α, the downstream factor of mutated IDH1, are found to be suppressed in IDH1 -mutant gliomas. Given the role of HIF-1α in cell migration, we conclude that the attenuation of HIF-1α-dependent glioblastoma cell infiltration contributes to the better outcomes of patients with IDH1 -mutant gliomas.